Computer Network Security and Preventive Measures in the Era of Big Data - Xiang, Jun (Journal of Theory and Practice of Engineering Science, 2024)
With the continuous development of networked information technology in China, the incidence of computer network security issues is also increasing. Once a computer encounters a network security issue, it will directly affect people's normal life and production. Therefore, computer users need to have strong awareness of network security management, take effective measures to prevent computer network security issues, and reduce the incidence of computer network security problems.